Two-dimensional nanoarchitectures for lithium storage - Liu, Jiehua. (2013)
Two dimensional nanoarchitectures are of great interest in lithium storage for energy-storage devices, in particular lithium-ion batteries, due to its shortened paths for fast lithium ion diffusion and large exposed surface offering more lithium-insertion channels. Their competitive lithium-storage features provide huge potentials to develop next-generation high-performance lithium-ion batteries. This review is devoted to the recent progress in the fabrication of innovative 2D structures with various synthetic strategies and their applications for lithium storage in lithium-ion batteries. These 2D architectures are categorized into six styles, i.e., nanoporous nanosheets, ultrathin nanosheets, flower-like structures assembled by nanosheets, sandwich-like nanosheets, corrugated nanosheets, and nanosheets with specific facets. Based on the lithium-storage manner, we further summerized their electrochemical performance for lithium storage with four classified themes including surface Li storage, zero or low-strain Li storage, volume-variation Li storage and synergic-effect Li storage. Finally, the outlook and perspective on 2D lithium-storage materials is concisely provided.